Closure Techniques and Postoperative Outcomes of Major Lower Limb Amputation in Acute Limb Ischemia - Khadafy, Reza; Hapsari, Putie; Utomo, Hafidh Seno Radi (Majalah Kedokteran Bandung, 2025)
Amputation, derived from the Latin "amputare," refers to the removal of a body part covered by skin, often necessitated by acute limb ischemia (ALI). Effective wound closure is critical for minimizing complications, length of stay, costs, and the risk of re-amputation. This study compared postoperative outcomes of major lower limb amputation in ALI patients with primary versus delayed wound closure. A descriptive analytic study was conducted at Dr. Hasan Sadikin Hospital, Bandung, Indonesia, from January 2020 to December 2023, analyzing medical records of 46 patients aged 19–85 years, with a predominance of female patients. Thrombosis was the leading cause of ALI (76.1%), and hypertension was the most frequent comorbidity. Significant differences were observed in stump complications and revision surgery rates between primary and delayed wound closure groups (p<0.05), while length of stay and mortality did not show statistically significant differencesy. In conclusion, the study highlights a significant relationship between different wound closure methods and complications, suggesting that choice of closure technique may influence the postoperative outcomes in ALI patients.